2021
DOI: 10.3390/ijerph18115698
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Soil Flushing with Tannic Acid and Its Effect on Metal Mobilization and Selected Properties of Calcareous Soil

Abstract: Cadmium, Cu, Ni, Pb, and Zn removal via soil flushing with tannic acid (TA) as a plant biosurfactant was studied. The soil was treated for 30 h in a column reactor at a constant TA concentration and pH (3%, pH 4) and at variable TA flow rates (0.5 mL/min or 1 mL/min). In the soil leachates, pH, electrical conductivity (EC), total dissolved organic carbon, and metal concentrations were monitored. Before and after flushing, soil pH, EC, organic matter content, and cation exchange capacity (CEC) were determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…However, the stability of external organic carbon in biosurfactant-washed soil needs further investigations. Our previous work demonstrated that tannic acid used for flushing metals from contaminated soil increased soil organic matter from 4.1% (unflushed soil) to 10.4–10.8% (flushed soil) [ 57 ]. Tannins can take part in the formation of humic-like substances because reactive quinones from tannins can self-polymerize or co-polymerize with other compounds such as amino-containing compounds [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the stability of external organic carbon in biosurfactant-washed soil needs further investigations. Our previous work demonstrated that tannic acid used for flushing metals from contaminated soil increased soil organic matter from 4.1% (unflushed soil) to 10.4–10.8% (flushed soil) [ 57 ]. Tannins can take part in the formation of humic-like substances because reactive quinones from tannins can self-polymerize or co-polymerize with other compounds such as amino-containing compounds [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soil-washing is a batchtype treatment method in which the soil and washing solution are thoroughly mixed, whereas soil-flushing is a column-type treatment method in which the solution is percolated through the soil. The soil-flushing has the advantage of consuming less eluent and having lower operating costs than soil-washing [19,20]. Even when U(VI) is removed from the soil, the wastewater from wet soil decontamination is a secondary waste and requires remediation.…”
Section: Introductionmentioning
confidence: 99%